Characteristics of seaweed caraginan Kappaphycus alvarezii on cultivation system with different seed weight - Muhammad Rasnijal; Ardana Kurniaji; Anton Anton; Budiyati Budiyati; Diana Putri Renitasari; Achmad Suhermanto; Mugi Mulyono; Iin Siti Djunaidah; Sinung Rahardjo; Sinar Pagi Sektiana; Ridwan Ridwan (Jurnal Akuakultur Indonesia)
Seaweed (Kappaphycus alvarezii) could be a source of carrageenan needed for industrial sector. The purpose of this study to analyze the characteristics of carrageenan seaweed cultivated with bag and non-bag cultivation systems and different seed weights. The research was conducted in the waters of Bone Bay and the Laboratory of the Indonesian Center for Brackish Water Cultivation and Fisheries Extension in Maros. This study used a factorial completely randomized design (CRD) consisting of factor A (using bags and non-bags), and factor B (seed weight 15, 50, 75, 100, and 125 g). The results showed that the cultivation method factor, seed weight factor, and their interaction had an effect on carrageenan yield, gel strength, ash content and water content (P <0.05). Different cultivation systems with different initial seed weight combinations showed different best results for each parameter. The highest value of yield of carrageenan was observed in the bag culture system with a seed weight of 100 g, namely 29.18 ± 1.10%. The highest value of gel strength was observed in the non-bagged cultivation system with a seed weight of 75 g, namely 1344.69 ± 18.43 g/cm2. The highest value of ash content was found in the non-bagged cultivation system with 125 g of seed weight, namely 30.02 ± 0.13%. The highest value of water content was found in the bag culture system at a seed weight of 15 g, namely 38.63 ± 0.26%. Different cultivation methods and seed weight resulted in other carrageenan characteristics of seaweed for each parameter.